LKPD Berbasis STEM untuk Melatih Kemampuan Berpikir Kreatif pada Materi Fiber Optic - Shanti Diah Ayu Kusumaningtias; Puji Rahayu Ningsih (Universitas Hamzanwadi, 2022)
LKPD is a student worksheet which is a sheet containing questions and assignments to activate students. The purpose of this study was to develop STEM-based worksheets for creative thinking about fiber-optic material in Vocational school (SMK), to test the feasibility level of LKPDs, and to analyze student responses to the use of LKPDs. The study used the ADDIE model with five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include structured interviews and closed questionnaires on a scale of five. The data analysis uses descriptive data to analyze, media validity, student responses, and questions. The results of the development in the form of LKPD STEM Creative Thinking Fiber Optics with the percentage of eligibility for validation by material experts (88%) and media experts (87.8%) are very valid categories and can be used without revision. Meanwhile, the results of the readability test (98.3%) and attractiveness (83.5%) were declared valid categories that could be used without revision. The percentage of validity test is seven-item (valid), two items (invalid), as well as the high category. Furthermore, the results of the discriminatory analysis obtained one and two items in the good category, and six items in the poor category.